PENGARUH BRAND IMAGE DAN PROMOSI ONLINE TERHADAP KEPUTUSAN PEMBELIAN PADA DISTRO FINDS SUPPLY GIANYAR - Boga Tirtawan, I Kadek; Handayani, Made Mulia (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
In today's times, consumersxare veryxcritical inchoosing a product, thexdecision toxbuy a product is stronglyx influenced by variousxforms of evaluation of the product. The purpose of this study was toxdetermine thexeffect of brandximage and onlinexpromotion partiallyxand simultaneouslyxon purchasing decisionsxat Finds Supply Gianyar Distro. Thexsample in thisxstudy were consumersxwho had purchasedxproducts andxvisited Finds Supply Distros, totaling 110 respondents. Determinationxof the numberxof respondents (sample) wasxcarried out using purposivexrandomxsampling. Data were analyzedxusing multiplexlinearxregression analysis, determination analysis, ttestxstatistical analysis (t-test), and Ftest statisticalxanalysis (F-test). The results showed that there was a partialxandxsimultaneous positivexandxsignificant influence between brandximage and onlinexpromotion on purchasingxdecisions at Distro Finds Supply Gianyar.